Seesjärveläisten itkijöiden rekisterit : Tutkimus äänellä itkemisen käytänteistä, teemoista ja käsitteistä - Stepanova, Eila (Suomen Kansantietouden Tutkijain Seura, 2014)
This thesis concentrates on the lament genre of Karelian oral poetry and the speech register distinctive of it. Laments can be defined as sung poetry of varying degrees of improvisation, which nonetheless follows conventionalized rules of traditional verbal and non-verbal expression, most often performed by women in ritual contexts and potentially also on non-ritual grievous occasions. The study focuses on the Seesjärvi region (Republic of Karelia, Russian Federation), with a corpus of 446 documented laments from 58 lamenters. Of these laments, one was recorded in 1871, and the rest during the period 1937-2007. The approach to this topic differs from previous research in two significant ways. First, emphasis is placed on the lamenters who used this poetry, how they understood it and used it both socially and also individually. Second, the study employs a theoretical and analytical framework that was not used in earlier research. This framework makes it possible to look closely at the use of laments by individual lamenters in practice and also at the genre, its speech register s potential to produce and communicate meanings as well as knowledge and understandings about the mythic world. This is done by triangulating three interrelated aspects of the tradition. These are the lament register, which is made up of the language, grammar, poetics and performance features of the genre; the lament themes and compositional structures; and the mythic conceptions of laments, which are forms of knowledge and understanding of the unseen world that are actualized and communicated through lament performance. Interaction is fundamental to the lament tradition. The lament register was, first and foremost, a ritual variety of language with an exceptional capacity for honorific interaction with unseen powers in the otherworld. It was also a resource for moderating and mediating individual as well as communal expressions of grief. The register and genre of laments is internalized and developed on the basis of individual experience. ...